PROTEST PARADIGM IN ETHNIC RIOTS NEWS (FRAMING ANALYSIS OF PAPUANS’ STUDENT DORMITORY RIOTS IN SURABAYA ON TABLOID JUBI (JUBI.CO.ID) IN AUGUST 2019) - Putri Laksmi Nurul Suci; Zainuddin Muda Z Monggilo (Master of Communication Science Program, Universitas Diponegoro, 2023)
In August 2019, the conflict between Papuan students and police happened in the Papuan students' dormitory in Surabaya, caused by misconceptions of information between both parties. This conflict triggered more riots in several cities, acts of racism, violence, and internet access blocking in Papua's region. Each media has its own frame and depiction of the purpose of this conflict. In the media, as a minority, Papuan students are depicted in different ways than usual. Therefore, this study aims to examine the depiction and frame of the Papuans' student dormitory riot that is reported on Tabloid Jubi (jubi.co.id) as ethnic minority media. This article uses eight pieces of online news from Tabloid Jubi (jubi.co.id), which will be analyzed using Pan and Kosicki framing analysis. In addition, this article also uses the concept of the protest paradigm from McLeod and Hertog (1998) to examine the tendency of how Tabloid Jubi (jubi.co.id) depicts information about riots. The result shows that Tabloid Jubi (jubi.co.id) tends to use three out of five characteristics in the concept of the protest paradigm, which are news frames, invocation of public opinion, and demonization.